QUALITY COMPARISON OF DUPLEX CARTON 350 GR/M2 BASED ON SNI-0123: 2008 - Lala Hucadinota Ainul Amri; Mawan Nugraha; Nazula Nurul Zahra (Kreator, 2020)
Duplex cartons will be one type of carton that is widely used as a primary or second packaging. Duplex cartons have hygroscopic properties that can be salted on the physical and quality of the carton duplex. The value of this Final Task paper is the way of quality of cardboard in the field and the efforts of the process and who is in the field champion of The Indonesian National Standard (SNI 0123:2008). While the purpose of this writing is For those who know the process of creation of duplex carton quality 350 gr / m2, To understand the results of the creation of the quality of both duplex cartons from different companies, and For to dye the quality of cartons 350 gr / m2 in the market of different companies. Which method in writing this Final Task paper is the Task Related to Indonesian National Standards (SNI 0123:2008). Located from the creation and duparan quality of its own results, the two duplex cartons there are different qualities, for the production of PT X. Cobb value which is passionate and quality questions according to SNI 0123:2008 while for the production of PT Y. brightness value who can not be questioned sni 0123:2008. SNI 0123:2008 was prepared with the purpose of standardization, but the standard provisions were not met and not supervised in companies that do not apply sni standard 0123:2008, but in companies that apply sni standard 0123:2008 found also incompatible, therefore it is recommended to be carried out monitoring periodically.Keywords— Quality duplex carton, Duplex Carton, SNI 0123:2008